Hemodialysis vascular access coordinator: Three‐level model for access management - Sousa, Clemente Neves (2023)
Management of vascular access is a challenge for the dialysis team, particularly tokeep the arteriovenous access working. The vascular access coordinator can posi-tively contribute to increase the number of arteriovenous fistulas and reduce centralvenous catheters. In this article, we introduce a new approach to vascular accessmanagement centered on (the results of setting up) the role of vascular access coor-dinator. We described the three-level model (3Level_M) for vascular access manage-ment organized in three levels: vascular access nurse manager, vascular accesscoordinator, and vascular access consultant. We defined the instrumental skills andtraining required to be developed by each element and clarify the articulationbetween the model and all members of the dialysis team related to vascular access.1|INTRODUCTIONThe implementation and effectiveness of renal replacement therapy(RRT) depend directly on appropriate vascular access, such as arterio-venous fistula (AVF) (best choice), or alternatively a graft or a centralvenous catheter (CVC).1Nowadays, chronic kidney disease (CKD) patients are older, sufferfrom a larger number of comorbidities, and have more complex vascu-lar accesses. Therefore, the dialysis team and patients face new chal-lenges. The complications of the arteriovenous accesses are alreadydocumented and require supervision (monitoring and surveillance) inorder to decide the appropriate time to intervene.1,2Literature shows that the vascular access coordinator canhave an important contribution in the identification ofthese situations and in the implementation of a new approachleading to the best results in clinical care.3–8The vascularaccess coordinator's role can be crucial to improve the planning oftimely interventions free of thrombosis,7,6improve vascular accessoutcomes,3,7decrease the number of grafts and CVCs,5and applya quality policy with the vascular access.6The purpose of thisarticle is to analyze the vascular access coordinator's contribution(to) in the vascular access outcomes and introduce a newapproach on vascular access management, the three-level model(3Level_M).Received: 12 February 2023 Revised: 22 March 2023 Accepted: 26 March 2023DOI: 10.1111/sdi.13153Semin Dial.2023;1–6.wileyonlinelibrary.com/journal/sdi© 2023 Wiley Periodicals LLC.1